2018
DOI: 10.1021/acs.orglett.8b01584
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric [4 + 2]-Cycloaddition of Copper–Allenylidenes with Hexahydro-1,3,5-triazines: Access to Chiral Tetrahydroquinazolines

Abstract: A copper-catalyzed asymmetric formal [4 + 2]-cycloaddition of copper-allenylidenes and hexahydro-1,3,5-triazines has been developed, providing chiral tetrahydroquinazolines in moderate to good yields and with high enantioselectivities for most cases (up to 88% yield and 98% ee).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(34 citation statements)
references
References 57 publications
0
33
0
1
Order By: Relevance
“…In the presence of phosphonate nucleophile, 2-phosphorylmethyl indoles could be produced with In the presence of suitable reagents, the decarboxylative annulation process using ethynyl cyclic carbamates proved to be a feasible method for the preparation of N-heterocycles. In this sense, different chemicals such as pyrazolones, hexahydro-1,3,5-triazines, azlactones, and C,N-cyclic azomethineimines were submitted for the reactions toward the formation of various N-heterocycles (Scheme 5) [25][26][27][28]. It is worth noting that the Wu group accomplished an enantioselective [4 + 2] cycloaddition reaction of ethynyl benzoxazinanones and silyloxyfurans toward the formation of tetrahydroquinolines featuring three stereo carbon centers [29].…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of phosphonate nucleophile, 2-phosphorylmethyl indoles could be produced with In the presence of suitable reagents, the decarboxylative annulation process using ethynyl cyclic carbamates proved to be a feasible method for the preparation of N-heterocycles. In this sense, different chemicals such as pyrazolones, hexahydro-1,3,5-triazines, azlactones, and C,N-cyclic azomethineimines were submitted for the reactions toward the formation of various N-heterocycles (Scheme 5) [25][26][27][28]. It is worth noting that the Wu group accomplished an enantioselective [4 + 2] cycloaddition reaction of ethynyl benzoxazinanones and silyloxyfurans toward the formation of tetrahydroquinolines featuring three stereo carbon centers [29].…”
Section: Introductionmentioning
confidence: 99%
“…[2] Representative examples including the [3 + 2] cycloaddition, [3] [2 + 1 + 2] cycloaddition, [4] [2 + 2 + 2] cycloaddition, [5] [3 + 2 + 2] cycloaddition, [6] [4 + 3] cycloaddition, [7] [2 + 2 + 2 + 2] cycloaddition, [8] and [4 + 1]/[4 + 3] cycloaddition, [9] were sequentially investigated as valuable cycloaddition reactions for the synthesis or modification of drug or drug-like complex heterocyclic molecules. [10] Very recently, Liu and co-workers demonstrated an inverse-electron-demand [4 + 2]-cycloaddition of in-situ formed aza-o-quinone methides with 1,3,5-triazinanes, leading to tetrahydroquinazolines in high yields (Scheme 1c). In 2017, Werz et al reported a MgI 2 -promoted [4 + 2]-cycloaddition of donor-acceptor cyclobutanes with 1,3,5-triazines to access piperidine derivatives (Scheme 1a).…”
mentioning
confidence: 99%
“…[3a] Shortly thereafter, the group of Sun reported [4 + 2]-cycloaddition of copper-allenylidenes with 1,3,5-triazines, which offered an efficient route to access chiral tetrahydroquinazolines with high enantioselectivities (Scheme 1b). [10] Very recently, Liu and co-workers demonstrated an inverse-electron-demand [4 + 2]-cycloaddition of in-situ formed aza-o-quinone methides with 1,3,5-triazinanes, leading to tetrahydroquinazolines in high yields (Scheme 1c). [11] Despite these impressive advances, the reported [4 + 2]-cycloaddition processes generally require the use of transition-metal catalysts or bases to promote the formation of the key four-atom cycloaddition partners.…”
mentioning
confidence: 99%
“…Seidel developed a 1,6‐hydrogen transfer based ring‐fused aminals of nitrogen heterocycles to construct tetrahydoquinazolines (Scheme ) . Recently, Sun and co‐workers reported [4+2]‐cycloaddition of copper‐allenylidenes with hexahydro‐1,3,5‐triazines to access chiral tetrahydroquinazolines . Despite these splendid advances, the development of novel approaches for the assembly of biologically promising tetrahydro‐quinazolines remains highly desirable and challenging.…”
Section: Figurementioning
confidence: 99%
“…[9] Recently, Sun and co-workers reported [4 + 2]-cycloaddition of cop-per-allenylidenes with hexahydro-1,3,5-triazines to access chiral tetrahydroquinazolines. [10] Despite these splendid advances, the development of novel approaches for the assembly of biologically promising tetrahydro-quinazolines remains highly desirable and challenging.…”
mentioning
confidence: 99%